2021
DOI: 10.1002/mma.7769
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of the dynamics of COVID‐19 in Africa under the influence of asymptomatic cases and re‐infection

Abstract: and only less than 5% of the 15 million cases were recorded in Africa. A major call for concern was the significant rise from 2% in May 2020 to 4.67% by the end of July 15, 2020. This drastic increase calls for quick intervention in the transmission and control strategy of COVID-19 in Africa. A mathematical model to theoretically investigate the consequence of ignoring asymptomatic cases on COVID-19 spread in Africa is proposed in this study. A qualitative analysis of the model is carried out with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Several reasons have been suggested for the low prevalence of SARS CoV-2 infection in Africa, one of which is the low testing capacity due to the fragile health system and exiguous molecular laboratories [2][3][4][5]. Although studies have shown that over 80% of persons infected with the virus were asymptomatic [6][7][8][9][10], most of the tests conducted in African countries were among people with symptomatic infections [4,7,[11][12][13][14].…”
Section: Recruitment Of Participants Sample Collection and Processingmentioning
confidence: 99%
“…Several reasons have been suggested for the low prevalence of SARS CoV-2 infection in Africa, one of which is the low testing capacity due to the fragile health system and exiguous molecular laboratories [2][3][4][5]. Although studies have shown that over 80% of persons infected with the virus were asymptomatic [6][7][8][9][10], most of the tests conducted in African countries were among people with symptomatic infections [4,7,[11][12][13][14].…”
Section: Recruitment Of Participants Sample Collection and Processingmentioning
confidence: 99%
“…The study was conducted for the entire African continent and does not specify how it affects Kenya as a country. Since it is only a speculation as to whether there is reinfection or not, this study is modification of the work of [9] with the following assumptions;…”
Section: Introductionmentioning
confidence: 99%
“…The outbreak started as an epidemic in Wuhan, China. Considering the rapid rate at which COVID-19 was transmitted, WHO declared COVID-19 a pandemic on 11th of March, 2020 by the World Health Organisation[9]. It is referred to as Severe Acute Respiratory Syndrome coronavirus-2 (SARS-CoV-2) by the International Committee for Taxonomy of Viruses and there is a high tendency it originates from the bat since 96% genome sequence…”
mentioning
confidence: 99%
“…A SIR transmission model has been utilized for decision-making on lockdowns during the COVID-19 pandemic [20]. Asymptotic stability analysis of disease-free and endemic equilibria using the SEIR transmission model has been applied to establish the influences of asymptomatic cases and reinfection [21]. SIR transmission explained through a logistic model has been adopted to describe and interpret a COVID-19 outbreak [22].…”
mentioning
confidence: 99%
“…For example, the forecasting models are the models with time independent variables such as the logistic and Gompertz models [1][2][3], the Bertalanffy model [4], the Boltzmann growth curve [5,6], and Regression analysis [7,8]. The mathematical models, a system of differential equations, are the models with time independent variable such SEIQCRW model [19], SIR model [20], SEIR model [21], and SEIQRD [24]. Most of these previous models are based on using time as the independent variable and do not involve distance and probabilistic analysis.…”
mentioning
confidence: 99%